Neurofilament light chain concentration mediates the association between regional cortical thickness and Parkinson’s disease with excessive daytime sleepiness - Chen, Jieyu; Jiang, Guoliang; Zhu, Yongyun; Liang, Chunyu; Liu, Chenxi; Chen, Jianzhun; Yang, Baiyuan; Yang, Xinglong (Frontiers in Aging Neuroscience, 2025)
BackgroundExcessive daytime sleepiness (EDS) is a common non-motor symptom in Parkinson’s disease (PD) that negatively impacts quality of life. Although biomarkers of brain structure, function, and neurodegeneration have been studied, their interactions in EDS remain unclear. This study explores the relationship between cortical thickness, functional connectivity (FC), and plasma neurofilament light chain (NfL) levels in PD-EDS.Methods36 PD-EDS patients and 100 PD patients without EDS (PD-non-EDS) underwent structural MRI and resting-state FC analysis, with regions of cortical atrophy serving as regions of interest (ROIs). Plasma NfL levels were quantified using high-sensitivity Single Molecule Array (SiMoA™). Mediation analysis was conducted to explore the interplay between NfL levels, neuroimaging markers, and EDS severity, assessed by the Epworth Sleepiness Scale (ESS).ResultsPD-EDS patients exhibited significant cortical thinning in the left supramarginal gyrus (SMG) and right postcentral region (PoCR), along with weakened FC between the left SMG and left PoCR, and between the right PoCR and left inferior frontal gyrus (all p < 0.05). Plasma NfL levels were significantly higher in PD-EDS patients than in those without EDS (p = 0.004) and mediated the relationship between left SMG thickness and EDS severity.ConclusionPlasma NfL levels mediate the association between cortical thinning in the left SMG and EDS severity in PD-EDS, suggesting a link between neurodegenerative processes underlying axonal injury and cortical atrophy in key regions associated with EDS in PD. Our findings suggest that combining neuroimaging markers with plasma NfL levels may provide valuable insights into the mechanisms driving EDS progression in PD.